Changing Perceptions, Changing Lives – Promoting Intercultural Competence and Ethical Creativity through Advertising. (31st July 2020) - Breninger, Birgit; Kaltenbacher, Thomas
Few phenomena have incited as much passion as the unravelling of 'creativity' and few disciplines have brought about so many controversial expressions of it as advertising. In the bio-cultural framework of Intercultural Competence® the co-emergence of 'ethical creativity' is conceived to be pivotal for intercultural expertise. We suspect that interculturally competent individuals more habitually engage in ethical creativity, that is, the co-activation of a creative mindset and a benevolent moral mindset informed by a difference-oriented mindset towards the 'familiar other' as well as the 'unfamiliar other'. In this framework, action is directly linked to perception, which, in turn, is influenced and shaped by the active creative mindset. To analyse ethical creativity as an intersecting process with the development of intercultural expertise, we designed and piloted a qualitative perceptuo-cognitive experiment including various advertising items to document the differences in perception of 34 leaders of small and medium enterprises and nongovernmental organisations (NGOs). The experiment consisted of 40 affective and culturalised visual items analysed with SR Research's Data Viewer software. The eyetracking data were translated and clustered into gaze types and combined with the response patterns from the questionnaire for analysis. 'Ethical creativity' is regarded as a dynamic process emerging through the co-activation of benevolent, moral mindsets. A specific perceptual architecture emerges from the convergence of various sets of expertise. The process of becoming interculturally competent and being able to enact ethical creativity is linked to advertising campaigns. Such interactions (of perception with activation of mindsets) have the potential to profoundly shape the behaviours and understandings of consumers.